The role of the definitions in the research in ontology (Perspectivas em Ciência da Informação, 2010)
Definition is investigated as an important issue for semantic expressiveness in ontologies. Studies reveal that current ontologies do not have standards for definitions. This raises the question of compatibility among vocabularies of systems working cooperatively, as is the case of researches developed in Bioinformatics. Literature presents some discussion of definitions in ontologies, specially analysing former definitions. Based on theoretical principles, our research aims at developing a suitable type of definition in the construction of consistent domain ontologies, i.e. operative definitions.